Moringa oleifera (drumstick tree)—nutraceutical, cosmetological and medicinal importance: a review - Klimek-Szczykutowicz, Marta; Gaweł-Bęben, Katarzyna; Rutka, Angelika; Blicharska, Eliza; Tatarczak-Michalewska, Małgorzata; Kulik-Siarek, Katarzyna; Kukula-Koch, Wirginia; Malinowska, Magdalena Anna; Szopa, Agnieszka (Frontiers in Pharmacology, 2024)
Moringa oleifera Lam. (Moringaceae) is a species of tree with an increasing utility, occurring naturally mainly in Pakistan and northern India. M. oleifera is currently cultivated in Africa, South America, Asia and the Middle East. The usage of its leaves, seed oil, bark, fruits, flowers and roots has positive opinions of FDA (American Food and Drug Administration), EFSA (European Food Safety Authority) and CosIng (Cosmetic Ingredients database). The chemical composition of M. oleifera is dominated by: proteins (consisting mainly of amino acids such as arginine or serine), fatty acids (omega-3 and omega-6), vitamins (vitamin A, B and C and tocopherols), mineral salts (including several bioelements, such as calcium, magnesium, sodium, and potassium), valuable polyphenolic compounds from the group of phenolic acids (e.g. gallic acid, ferulic acid) and flavonoids (e.g. myricetin, rutoside, and kaempferol). The raw materials show antioxidant, hepatoprotective, anti-inflammatory and antimicrobial properties. Dietary supplements and alimentary products containing M. oleifera are recommended as health-promoting and "novel food" preparations. The main purpose of this work was a review of the latest scientific literature on M. oleifera, with particular emphasis on the studies focusing on its chemical composition, biological activity and safety. Moreover, the review tends to discuss the results of biotechnological studies using this material and the agronomical significance.